2017
DOI: 10.4103/ijo.ijo_485_17
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography features of acute macular neuroretinopathy in dengue fever

Abstract: A 39-year-old female with dengue fever presented with decreased vision in both eyes. Visual acuity was 20/200 and 20/80 in the right eye (OD) and left eye (OS), respectively. Fundus showed granular, grayish-white lesions in the parafoveal region in OD. Multimodal imaging including optical coherence tomography angiography (OCTA), optical coherence tomography (OCT), and fluorescein angiography (FA) was performed. FA showed late hyperfluorescence with few microaneurysms in OS. OCT showed hyperreflectivity in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 10 publications
(12 reference statements)
0
13
0
Order By: Relevance
“…Changes in OCTA in the SCP and DCP were noted in dengue and chikungunya retinitis. [678] Agarwal et al in their report on OCTA features of chikungunya retinitis reported that there were flow void areas in SCP, DCP, and choriocapillary slabs. [6] Aggarwal et al in their report on OCTA features of acute macular neuroretinopathy post-dengue fever noted flow deficit areas in SCP and DCP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in OCTA in the SCP and DCP were noted in dengue and chikungunya retinitis. [678] Agarwal et al in their report on OCTA features of chikungunya retinitis reported that there were flow void areas in SCP, DCP, and choriocapillary slabs. [6] Aggarwal et al in their report on OCTA features of acute macular neuroretinopathy post-dengue fever noted flow deficit areas in SCP and DCP.…”
Section: Discussionmentioning
confidence: 99%
“…They did not report any changes at the level of choriocapillary. [7] Bajgai et al noted broken foveal avascular zone in only SCP of OCTA in a case of dengue maculopathy and these changes persisted at follow-up visits. [8]…”
Section: Discussionmentioning
confidence: 99%
“…3 Aggarwal et al and Liu and colleagues used OCTA to monitor improvement in retinal capillary disruption in patients with acute macular neuroretinopathy with and without treatment with oral steroids, respectively. 5,6 OCTA of our patient showed improvement in her superficial and deep capillary plexus deficits with a granularity finder than could be provided by FA months after treatment while her vision and other retinal lesions also improved. OCT was inadequate to monitor her posttreatment improvement of edema and accurately observe the degree of active ischemia and vasculitis.…”
Section: Discussionmentioning
confidence: 46%
“…5 OCTA may also be used to evaluate the impact of treatment on the restoration of blood flow. 6 We present the first reported case to our knowledge of mixed connective tissue disease (MCTD)-associated retinal vasculitis monitored by OCTA with findings characteristic of occlusive vasculitis that demonstrated improvement in pathologic blood flow over the course of systemic and local treatment.…”
Section: Introductionmentioning
confidence: 97%
“…Dengue fever, an arthropod-borne disease, caused by four serotypes of Dengue virus, can manifest various ophthalmologic symptoms, such as subconjunctival hemorrhage, keratitis, anterior uveitis, angle-closure glaucoma as for anterior segment and, more commonly, ME, retinal hemorrhages, foveolitis, cotton wool spots, AMN lesions, and microaneurysms as for posterior segment involvement [98]. Deduced from case reports, OCTA has proven to be a worthy diagnostic tool for detecting flow deficits in the perifoveal region within the DCP and SCP in ischemic inflammatory foveolitis and outer maculopathy, even when fundus lesions were not detectable [98100].…”
Section: About the Implementation Of Optical Coherence Tomography Angmentioning
confidence: 99%